Reducing Bandwidth Blocking Rate in Elastic Optical Networks Through Scale-Based Slicer Placement Strategy - Nattapong Kitsuwan; Praphan Pavarangkoon (IEEE Access, 2023)
In this paper, we present a scale-based slicer placement strategy aimed at decreasing the bandwidth blocking rate (BBR) in elastic optical networks (EONs). EONs adopt slicing-and-stitching technology to bypass the requirement of consecutive spectrum slots on the same link for a single request. This is achieved through the use of slicers to split the requested spectrum band into multiple sub-spectrum components. However, a uniform distribution of slicers across all nodes may not guarantee low BBR due to varying traffic volumes on each node. Our proposed scale-based policy determines the necessary number of slicers for each node based on our investigation. Simulation results demonstrate that our strategy leads to a 91% reduction in BBR compared to conventional methods.
Keywords: Advanced Optical Network Technologies; Optical Network Technologies; Advanced Photonic Communication Systems